AKAR HISTORIS PENGADILAN AGAMA MASA ORDE BARU - Moh Sutomo; Syarifah Marwiyah; Nur Mawaddah Warohmah (Program Studi Hukum Keluarga Islam, 2016)
This is a library research on the history and development of the Religious Court in Indonesia and its existence and competence which is unseparable from political will of the government. This article focuses on the New Order era and devides the discussion into three sub-sections: first, regulations, laws and competencies of the Religious Court, secondly position of the Religious Court based on the Law No 14 of 1970 and Law No 1 of 1974; and third, existence of the Religious Court after the Law No 7 of 1989